JOMH 2020
DOI: 10.31083/jomh.v17i1.302
|View full text |Cite
|
Sign up to set email alerts
|

Age score for assessing motor function in Chinese older men

Abstract: Background and objective: Motor performance plays an important role in daily activities for older adults. The purpose of the study was to construct a method for measuring physical fitness age that can be used to assess motor performance in elderly men and to verify its validity. Methods: Four items of physical fitness including grip strength, balancing on one leg with eyes open, 30 s chair stand test and 6 min walk test were selected and measured in a random order. Principal component analysis was employed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It is known that exercise can improve respiratory function and quality of life (Chan et al, 2013;Papp et al, 2017;Yang et al, 2020;Zhao et al, 2021). Dogra et al (2019), for instance, demonstrated that 30 min of physical activities each day could lead to a rise in FEV 1 /FVC in both healthy adults and patients with obstructive lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that exercise can improve respiratory function and quality of life (Chan et al, 2013;Papp et al, 2017;Yang et al, 2020;Zhao et al, 2021). Dogra et al (2019), for instance, demonstrated that 30 min of physical activities each day could lead to a rise in FEV 1 /FVC in both healthy adults and patients with obstructive lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The total number of seconds was recorded from the time of eyes closing to the point where body balance was lost. Regarding the other physical fitness measurements, a full description for each measurement can be obtained from our previous studies (Takeshima et al, 2002;Zhao et al, 2017Zhao et al, , 2018Zhao et al, , 2020Zhao, Huang, Gu, et al, 2021).…”
Section: Physical Fitness Measurementsmentioning
confidence: 99%